Pengaruh Manajemen, Kepemimpinan dan Motivasi Kepala Sekolah terhadap Pengembangan Kompetensi Guru Sekolah Menengah Atas Negeri di Kota Tanjungbalai - Maskur Yus; Elfrianto Elfrianto; Sri Nurabdiah Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the influence of the management, leadership and motivation of the principal on the development of the competence of SMA Negeri teachers in Tanjungbalai City. This research uses quantitative research methods. The sample of this research is 159 SMA Negeri teachers in Tanjungbalai City. The data collection technique used a questionnaire which was measured by a Likert scale. Data analysis was done by using multiple linear regression analysis technique. The results showed that the influence of the management, leadership and motivation of the principal on the development of the competence of SMA Negeri teachers in Tanjungbalai City, based on the following indicators: First, there is a positive and significant influence of principal's management on the development of the competence of SMA Negeri teachers in Tanjungbalai City, meaning that the more good management of the principal, the competence of teachers will be better and develop. Second, there is a positive and significant influence on the leadership of the Principal on the development of the competence of SMA Negeri teachers in Tanjungbalai City, meaning that the better the leadership of the principal, the competence of the teacher will be better and develop. Third, there is a positive and significant influence on the principal's motivation on the development of the competence of SMA Negeri teachers in Tanjungbalai City, meaning that the better the principal's motivation, the teacher's competence will be better and develop. Fourth, there is a positive and significant influence on the management, leadership and motivation of the principal simultaneously on the development of the competence of SMA Negeri teachers in Tanjungbalai City, meaning that the better the management, leadership and motivation of the Principal, the teacher's competence will be better and develop. Keywords: Management, Leadership, Principal Motivation, Teacher Competence